2014
DOI: 10.1002/pro.2519
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of double‐stranded DNA with polymerized PprA protein from Deinococcus radiodurans

Abstract: Pleiotropic protein promoting DNA repair A (PprA) is a key protein that facilitates the extreme radioresistance of Deinococcus radiodurans. To clarify the role of PprA in the radioresistance mechanism, the interaction between recombinant PprA expressed in Escherichia coli with several double-stranded DNAs (i.e., super coiled, linear, or nicked circular dsDNA) was investigated. In a gel-shift assay, the band shift of supercoiled pUC19 DNA caused by the binding of PprA showed a bimodal distribution, which was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
(89 reference statements)
1
11
0
Order By: Relevance
“…The polymerization of PprA depends on the concentration of the protein. Whereas PprA binds to dsDNA to form an unsaturated nucleoprotein complex at low concentrations, a larger nucleoprotein complex is formed to facilitate the association of the ends of damaged DNAs at high concentrations [54 ]. Analyses of the cellular dynamics of PprA have indicated the interactions of PprA with topoisomerase (Topo IB) and DNA gyrase, suggesting the significant role of PprA in preserving genome integrity following irradiation [55][56][57].…”
Section: Current Opinion In Microbiologymentioning
confidence: 99%
“…The polymerization of PprA depends on the concentration of the protein. Whereas PprA binds to dsDNA to form an unsaturated nucleoprotein complex at low concentrations, a larger nucleoprotein complex is formed to facilitate the association of the ends of damaged DNAs at high concentrations [54 ]. Analyses of the cellular dynamics of PprA have indicated the interactions of PprA with topoisomerase (Topo IB) and DNA gyrase, suggesting the significant role of PprA in preserving genome integrity following irradiation [55][56][57].…”
Section: Current Opinion In Microbiologymentioning
confidence: 99%
“…Although mutations on Ala139 and Trp183 residues inside the protein molecule lost the DNA binding ability by disruption of PprA oligomerization, mutations on the molecular surface near Interface 2 without the disruption of oligomerization may lead to investigating effects of interactions between PprA and gyrase to radioresistance. The binding affinity of PprA, however, is similar for linear and supercoiled DNA (33). PprA therefore seems not to assist DNA relaxation with the deformation of DNA but is a DNA guide for gyrase.…”
Section: Discussionmentioning
confidence: 89%
“…Wild-type PprA exhibits a wide range of oligomeric structures, even without binding to DNA, and the molecular size of the oligomers is estimated to be from 1 3 10 5 to 3 3 10 6 Da (tetramer to 100-mers), depending on the protein concentration (33). Attempts to crystallize wildtype PprA yielded a rod-shaped single crystal (Supplemental Fig.…”
Section: Tertiary Structure Of Mutant Ppra Obtained By Random Mutagenmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro , PprA preferentially binds double-stranded DNA (dsDNA) carrying strand breaks, inhibits Escherichia coli exonuclease III activity, and stimulates the DNA end-joining reaction catalyzed by ATP-dependent DNA ligases ( 14 ). It has also been shown that PprA polymerizes along supercoiled, nicked, circular, or linear double-stranded DNA ( 23 ). After irradiation, PprA is part of a multiprotein complex containing 24 proteins, including DNA ligases, DNA topoisomerase IB (Topo IB), SSB, and DNA polymerase I and exhibiting both DNA synthesis and DNA end-processing functions ( 24 ).…”
Section: Introductionmentioning
confidence: 99%